Reading Strategies of Multilingual ESL Learners across Culturally Familiar and Unfamiliar Texts in Eswatini - Mfanukhona Wonderboy Kunene; Nicholus Nyika (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Reading comprehension in multilingual contexts requires more than linguistic competence; it demands metacognitive regulation and strategic flexibility across culturally diverse materials. This study investigates the reading strategies employed by Eswatini English as a Second Language (ESL) learners when engaging with culturally familiar and culturally unfamiliar texts, addressing the limited evidence on strategy transfer within multilingual African contexts. A quantitative repeated-measures design was used with 200 Eswatini senior secondary learners, who each read two passages matched in length and readability, one culturally familiar and one culturally distant, and reported their strategy use using the Survey of Reading Strategies (SORS). Results revealed moderate and stable engagement across Global, Support, and Problem-Solving strategies, with Problem-Solving strategies employed slightly more frequently but without statistically significant differences between text types. Correlational analyses indicated a moderate relationship between familiar and unfamiliar text strategy use, suggesting that learners relied on habitual, routine behaviours rather than adaptive, metacognitively guided strategies. Based on these findings, the study proposes the Strategic Engagement and Transfer (SET) Model, which conceptualises a developmental progression from habitual, inconsistent strategy use to conscious, context-aware deployment, and ultimately integrated, automatic strategic competence. The findings inform English Language Teaching (ELT) by offering a context-sensitive metacognitive framework for scaffolding strategy instruction, promoting adaptive engagement, and fostering transferable reading competence across culturally diverse texts.